Curcumin: A Challenge in Cancer Treatment - Basnet, Purusotam; Skalko-Basnet, Natasa (Journal of Nepal Pharmaceutical Association, 2012)
Oxidative damage initiates the inflammation and inflammation has been pointed out as the root cause of cancer and various other chronic diseases such as diabetes, hypertension, Alzheimer’s disease, etc. Epidemiological and clinical studies have suggested that cancer could be prevented or significantly reduced by appropriate treatment with anti-oxidant and anti-inflammatory drugs. Therefore, curcumin, a principal component of turmeric (curry spice) exhibiting strong anti-oxidant and anti-inflammatory activities, might be a potential candidate for the prevention and/or treatment of cancer and other chronic diseases. However, curcumin, in spite of its excellent safety profile, multitargeting effects and strong evidences on the molecular levels, could not achieve the desired therapeutic outcome in the past clinical trials, mainly due to its low solubility and poor bioavailability. Curcumin can be developed as a therapeutic drug through improvement in formulation properties or delivery systems, enabling its enhanced absorption and cellular uptake. This review mainly focuses on its anti-oxidant and anti-inflammatory potentials and recent developments in dosage form and delivery systems, opening the possibilities of therapeutic application of curcumin in the prevention and/or treatment of cancer.DOI: http://dx.doi.org/10.3126/jnpa.v26i1.6631 JNPA. XXVI(1) 2012 19-47